Elucidating the role of compression waves and impact duration for generating mild traumatic brain injury in rats. (2nd January 2017) - Lucke-Wold, Brandon P.; Phillips, Michael; Turner, Ryan C.; Logsdon, Aric F.; Smith, Kelly E.; Huber, Jason D.; Rosen, Charles L.; Regele, Jonathan D.
Abstract: Background : In total, 3.8 million concussions occur each year in the US leading to acute functional deficits, but the underlying histopathologic changes that occur are relatively unknown. In order to improve understanding of acute injury mechanisms, appropriately designed pre-clinical models must be utilized. Methods: The clinical relevance of compression wave injury models revolves around the ability to produce consistent histopathologic deficits. Mild traumatic brain injuries activate similar neuroinflammatory cascades, cell death markers and increases in amyloid precursor protein in both humans and rodents. Humans, however, infrequently succumb to mild traumatic brain injuries and, therefore, the intensity and magnitude of impacts must be inferred. Understanding compression wave properties and mechanical loading could help link the histopathologic deficits seen in rodents to what might be happening in human brains following concussions. Results : While the concept of linking duration and intensity of impact to subsequent histopathologic deficits makes sense, numerical modelling of compression waves has not been performed in this context. In this interdisciplinary work, numerical simulations were performed to study the creation of compression waves in an experimental model. Conclusion : This work was conducted in conjunction with a repetitive compression wave injury paradigm in rats in order to better understand how the wave generation correlates with histopathologic deficits.